2020
DOI: 10.1016/j.ctro.2020.02.003
|View full text |Cite
|
Sign up to set email alerts
|

Omission of postoperative radiation after breast conserving surgery: A progressive paradigm shift towards precision medicine

Abstract: Radiation therapy is a standard therapeutic option in the post-operative setting for early breast cancer patients after breast conserving surgery, providing a substantial benefit in reducing the risk of local relapse with a consequent survival gain. Nevertheless, the reduction in the burden related to treatment is becoming crucial in modern oncology for both local and systemic therapies and investigational efforts are being put forward by radiations oncologists to identify a subset of women at very low risk to… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
25
0

Year Published

2020
2020
2021
2021

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 26 publications
(25 citation statements)
references
References 69 publications
0
25
0
Order By: Relevance
“…Preoperative chemotherapy (PST) in breast cancer (BC) patients was historically used in locally advanced disease. More recently, it is increasingly being applied in earlier stage BC, although no advantage in survival was observed as compared to postoperative systemic therapy [ [1] , [2] , [3] , [4] ]. Several studies showed a survival benefit in patients with pathological complete response (pCR), except for luminal A-patients [ 5 , 6 ] suggesting that the response to PST may have clinical implications such as a higher chance to offer breast conserving therapy [ 7 , 8 ] and a less extensive treatment of the axilla, if after PST, tumor-positive (axillary) lymph nodes are converted into ypN0 [ 7 , [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…Preoperative chemotherapy (PST) in breast cancer (BC) patients was historically used in locally advanced disease. More recently, it is increasingly being applied in earlier stage BC, although no advantage in survival was observed as compared to postoperative systemic therapy [ [1] , [2] , [3] , [4] ]. Several studies showed a survival benefit in patients with pathological complete response (pCR), except for luminal A-patients [ 5 , 6 ] suggesting that the response to PST may have clinical implications such as a higher chance to offer breast conserving therapy [ 7 , 8 ] and a less extensive treatment of the axilla, if after PST, tumor-positive (axillary) lymph nodes are converted into ypN0 [ 7 , [9] , [10] , [11] , [12] ].…”
Section: Introductionmentioning
confidence: 99%
“…Studies have also suggested that RT may be omitted in selected elderly patients with low-risk disease (86). RT omission after breast-conserving surgery has also been explored in several randomized phase III trials; unfortunately, heterogeneous eligibility criteria across the trials has resulted in differing results with confounding interpretations (87). These types of studies have led to an increased interest in the development of radiation omission signatures specific for BC, whereby low-risk patients can be spared RT.…”
Section: Breast Cancer Specific Genomic Signaturesmentioning
confidence: 99%
“…Breast cancer is a paradigmatic example on how the radiotherapy decision-making process can be adapted to this particular situation and a proof of the versatility of radiation oncology treatment strategies, as pointed out in the guidelines for breast cancer during the COVID-19 pandemic [13]. Radiotherapy could be safely omitted, after breast conservation, for low-risk ductal in situ carcinoma or infiltrative disease with low-risk features (size ≤ 30 mm, node negative, G1-G2, clear resection margins, estrogen receptor positive, HER2 negative, in patients aged >65 planned to receive hormonal manipulation) [13,14]. When whole breast radiotherapy is indicated, 5 fractions can be used for node-negative patients not requiring a boost (28-30 Gy in once weekly fractions over 5 weeks as per FAST trial or 26 Gy in 5 daily fractions in 1 week as per FAST Forward trial).…”
Section: The Example Of Breast Cancermentioning
confidence: 99%